Application of Data Science in Circulating Tumor DNA Detection: A Promising Avenue Towards Liquid Biopsy - Li, Ming; Xie, Sisi; Lu, Chenyu; Zhu, Lingyun; Zhu, Lvyun (Frontiers in Oncology, 2021)
The circulating tumor DNA (ctDNA), as a promising biomarker of liquid biopsy, has potential clinical relevance on the molecular diagnosis and monitoring of cancer. However, the trace concentration level of ctDNA in the peripheral blood restricts its extensive clinical application. Recently, high-throughput-based methodologies have been leveraged to improve the sensitivity and specificity of ctDNA detection, showing a promising avenue towards liquid biopsy. This review briefly summarizes the high-throughput data features concerned by current ctDNA detection strategies and the technical obstacles, potential solutions, and clinical relevance of current ctDNA profiling technologies. We also highlight future directions improving the limit of detection of ctDNA for better clinical application. This review may serve as a reference for the crosslinks between data science and ctDNA-based liquid biopsy, which toward clinical translation in advanced cancer diagnosis.